Experimental and numerical investigation of expanding tubes - Ravindrababu Suraj (2016)
This study performs an experimental and numerical investigation of expanding metal tubes. Aluminium alloy 6063-T52 was chosen as the material as it is commonly available in the local industry. Parametric study was done in order to study the effect of various parameters and the effect of one parameter over the other was studied by applying Taguchi’s method of experiment approach. 3D models were modelled in the commercial finite element package ABAQUS^2xplicit. A converging model was obtained and this was incorporated with the Forming Limit diagram (FLD) failure criterion to study the load resisting capacity of such expanding tubes. Experiments were conducted on A16063-T52 tubes of outer diameter 50.8mm with wall thickness of 0.8mm and a length of 110mm. Instron 5500R testing machine was used for conducting the experiments. The FLD failure locus was also obtained numerically by using ABAQUS^Explicit package. Numerical results obtained were then validated with the experimental results. The study showed that the damage criteria based on the Forming Limit Diagram (FLD) can be successfully applied to predict the failure of expanding metal tubes. The results deviated by only 5%. An interesting method for predicting the forming limit curve numerically was obtained. Parametric study showed that the thickness of the tube affected the load absorbing capacity of the tube followed by the expansion ratio and then the punch angle of the die. A recommendation was made to use tubes with moderate thickness and high expansion ratio based upon the findings of Taguchi’s method of experiments method. Based upon this, certain design suggestions were also made in this project.